Using the M-score Model in Detecting Earnings Management: Evidence from Non-Financial Vietnamese Listed Companies - Nguyen, Huu Anh (H. : ĐHQGHN, 2017)
Earnings management is considered to be one of the most important issues related to financial statements, which has been well-documented in accounting theory and practice for a long time. Earnings management has become a critical topic in accounting, but few researchers have addressed this issue in the Vietnamese context. This paper examines earnings management detection among Vietnamese companies listed on the Hochiminh Stock Exchange (HOSE) by using the Beneish M-score model for a sample of 229 non-financial Vietnamese companies listed on the HOSE during 2013-2014. The results showed that 48.4% non-financial Vietnamese companies listed on the HOSE were involved in earnings management and the sample observations fit the Beneish M-score model. In conclusion, this study suggests that the M-score model is one of the useful techniques in detecting earnings manipulation behaviors of the companies and it could be applied for an improvement in financial reporting quality and a better protection for investors